Process improvements in magma and pele inkjet cartridge intermediate assembly (IA) production lines - Henry Suseno Nilam (2014)
Several main challenges are faced by the HP IA Department in its efforts to improve the process productivity for its latest inkjet generations, code named as Pele and Magma. These issues include understanding the lifted flex problem, quantifying the waviness in the flex and reducing the variability and cycle time in the encapsulation process through design of dual needle dispensing system and curing oven optimization. The lifted flex and the waviness in the flex have caused a decrease in the production yield at the IA and final assembly. Though some efforts had been put to solve these problems, they had not been completely eliminated due to lack of understanding of the root cause of the lifted flex and absence of a standard index to quantify the degree of flex waviness. In order to solve these issues, material analysis and experimentation were conducted to find the possible root cause of the problems, including tensile test, thermogravimetry analysis and chemical analysis. In order to establish a suitable flex waviness index, measurements were done for tensioned flexes using the coordinate measuring machine (CMM). Data analysis was performed and several indexes were explored including the R-squared regression index, the average roughness indexes (Ra and Rq) and the Fourier transform magnitude index. In addition to these two aspects, the project also aimed at improving the encapsulation process. Currently, the encapsulation process is the bottleneck among the IA processes. To reduce the cycle time of this process, the dual needle dispensing technique was explored as opposed to the current single needle system. The main challenge with this new technique was in balancing the microfluidic flow between the two needles to minimize the dispensing variability. Several mechanical changes were implemented and tested, taking into account the cost of manufacturing and the accessibility of the dispenser for cleaning. In line with the efforts to reduce the encapsulation cycle time, oven size optimization was conducted to minimize the oven length while still achieving the specified percent cure for the encapsulation. The optimization had to take into account the trade off between the line speed, the curing time (oven length) and the temperature. Design of experiments (DOE) were conducted to find the correlations between these factors and to find the optimized oven conditions. Looking at a broader perspective, the project also aimed at investigating the current available encapsulation technologies as well as the potential future technologies to meet the ever tighter specifications in the inkjet cartridge manufacturing.